2010
DOI: 10.5194/cp-6-1-2010
|View full text |Cite
|
Sign up to set email alerts
|

A unified proxy for ENSO and PDO variability since 1650

Abstract: Abstract. In this manuscript we have attempted to consolidate the common signal in previously defined proxy reconstructions of the El Niño-Southern Oscillation into one individual proxy titled the Unified ENSO Proxy (UEP). While correlating well with the majority of input reconstructions, the UEP provides better representation of observed indices of ENSO, discrete ENSO events and documented historical chronologies of ENSO than any of these input ENSO reconstructions. Further to this, the UEP also provides a me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
183
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(212 citation statements)
references
References 55 publications
28
183
1
Order By: Relevance
“…The NINO3.4 response found in this research supports previous studies by Adams et al (2003), Mann et al (2005), Emile-Geay et al (2008), McGregor et al (2010 and Maher et al (2015), despite GISS modelling weaker SST anomalies than observations (Fig. 1a, b).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The NINO3.4 response found in this research supports previous studies by Adams et al (2003), Mann et al (2005), Emile-Geay et al (2008), McGregor et al (2010 and Maher et al (2015), despite GISS modelling weaker SST anomalies than observations (Fig. 1a, b).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, a statistical relationship has been demonstrated between explosive tropical volcanism and ENSO where large tropical eruptions can increase the likelihood and amplitude of an El Niño event in following years, followed by a weaker La Niña state (Adams et al, 2003). Further work by Mann et al (2005), Emile-Geay et al (2008), McGregor et al (2010),812 S. A. P. Blake et al: Large volcanic eruptions of the last millennium (850-1850 CE) on Australian rainfall regimes result. Pausata et al (2015) and Stevenson et al (2016) identified that a radiative forcing threshold value of more than 15 W m −2 is required to affect the ENSO, and that high latitude Northern Hemisphere eruptions, in addition to tropical eruptions, are capable of doing so, as long as the forcing is asymmetric with regards to the equator.…”
Section: Introductionmentioning
confidence: 99%
“…2 demonstrates how miscounting errors may produce an apparent amplitude modulation of otherwise stationary signals, producing spurious trends in the average derived from them. Because climate reconstruction methods rely in some fashion on a weighted average of observations assumed to be contemporaneous, this may partially explain why many ENSO reconstructions (e.g., Mann et al, 2000;Wilson et al, 2010;McGregor et al, 2010;Li et al, 2011; display increasing trends in ENSO variance over time (McGregor et al, 2013). As pointed out in the latter study, computing ENSO variance on individual records prior to averaging them together is more robust to chronological errors.…”
Section: Discussionmentioning
confidence: 82%
“…Multiple ENSO and PDO reconstructions focused on the past millennium have been assembled in our previous work (Shi et al, 2017). Without loss of generality, we selected three reconstructed ENSO indices (Cook et al, 2008;McGregor et al, 2010;Li et al, 2013a) …”
Section: El Niño-southern Oscillation (Enso) and Pacific Decadal Oscimentioning
confidence: 99%